Analysis of the Availability of Healthcare Human Resources at Health Centers in Central Sulawesi Province for 2024 - Nurlia Lahay; Ketut Suarayasa; Abd Rahman (Faculty of Medicine, Universitas Tadulako, 2026)
Background: Equitable human resources for health (HRH) are essential for effective Puskesmas services, but aggregate workforce totals may conceal facility level gaps. Objective: To describe workforce composition and geographic distribution and quantify completeness of nine strategic health worker categories in Central Sulawesi Puskesmas in 2024. Methods: This descriptive secondary data study included all 219 operational Puskesmas. Actual 2024 HRH administrative records from the Central Sulawesi Provincial Health Office were analyzed using frequencies, percentages, and geographic ranges. Facility denominators and nine cadre completeness were reconciled with the official 2024 provincial health profile. Results: The nine health worker categories comprised 13,172 personnel. Midwives (5,043; 38.3%) and nurses (4,168; 31.6%) were the largest groups. Of 219 Puskesmas, 117 were inpatient and 102 non-inpatient. Only 96 facilities (43.8%) had all nine strategic workforce categories, while 123 (56.2%) lacked at least one. Dentists and medical laboratory technologists were the most frequently missing cadres. Workforce availability also varied geographically, indicating uneven staffing across districts and municipalities. Conclusion: Central Sulawesi has a substantial primary care workforce, but facility level completeness remains limited. Workforce planning should prioritize specific vacancies, equitable cadre distribution, and hard to reach settings rather than infer service readiness from provincial workforce totals alone.